Further results of fuzzy linguistic logic programming - Le, Hung Van; Tran, Khang Dinh (Journal of Computer Science and Cybernetics, 2014)
Fuzzy linguistic logic programming is introduced to represent and reason with linguistically-expressed human knowledge, where the truth of vague sentences is given in linguistic terms, and linguistic hedges can be used to indicate different levels of emphasis. Fuzzy linguistic logic programming has been shown to have fundamental notions and results of a logic programming framework, especially of the declarative semantics, procedural semantics, and fixpoint semantics. The procedural semantics are sound, complete and directly manipulates linguistic terms in order to compute answers to queries. In this paper, we prove some additional results of fuzzy linguistic logic programming, which can be considered as a counterpart of those of traditional definite logic programming. We also show that it has a generalized Pavelka-style completeness. Moreover, the possibility that aggregation operators can occur in rule bodies is also discussed.